(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Teaching English to beginners in Uzbekistan presents unique challenges and opportunities due to the country’s rich linguistic heritage and growing demand for English proficiency. This guide explores effective strategies for English language instruction, tailored specifically for beginners in Uzbekistan. It delves into understanding the learners’ cultural background, selecting appropriate teaching materials, integrating technology, and employing communicative teaching methods. By addressing these aspects, educators can create an engaging and supportive environment that fosters language acquisition and prepares students for a globalized world